Incorporating sustainability in business management in higher education : how educators and students need to adapt? - Córdova, Miguel (2022)
The grand challenges of our time require an educational overhaul, especially in business and management-related disciplines, which could play as a change maker towards more comprehensive strategies from organizations. Thus, this paper discusses why incorporating a sustainable perspective is urgently needed, details selected suggestions on how this process can be initiated, and identifies which benefits arise through rethinking business and management-related disciplines in the higher education sector. To achive this, recommendations for business management professors and suggestions for students are outlined in the conclusion.